2011
DOI: 10.1029/2011gc003553
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional FEM derived elastic Green's functions for the coseismic deformation of the 2005Mw8.7 Nias-Simeulue, Sumatra earthquake

Abstract: Using finite element models (FEMs), we examine the sensitivity of surface displacements to the location of fault slip, topography, and three‐dimensional variations in elastic moduli in the context of a 2‐D infinite thrust fault. We then evaluate the impact of these factors and fault geometry on surface displacements and estimates of the distribution of coseismic slip associated with the 2005 Mw 8.7 Nias‐Simeulue, Sumatra earthquake. Topographic effects can be significant near the trench, where bathymetric grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 43 publications
9
47
0
Order By: Relevance
“…They found the maximum difference is about 5% and mainly localized near the trench where the topographic gradient is highest. Basically the present conclusions coincide with that of Hsu et al (2011), although both studies are made for different targets and different topographical models. Thus, we conclude that the terrain effect must be considered in the application of dislocation theory to calculate the co-seismic and post seismic deformation.…”
Section: Case Study: Wenchun Earthquakesupporting
confidence: 77%
See 1 more Smart Citation
“…They found the maximum difference is about 5% and mainly localized near the trench where the topographic gradient is highest. Basically the present conclusions coincide with that of Hsu et al (2011), although both studies are made for different targets and different topographical models. Thus, we conclude that the terrain effect must be considered in the application of dislocation theory to calculate the co-seismic and post seismic deformation.…”
Section: Case Study: Wenchun Earthquakesupporting
confidence: 77%
“…Results show that the relative impact is 9.05% of the horizontal direction and 2.95% of the vertical direction. Hsu et al (2011) also studied the impact of topography on surface displacement using a three-dimensional FEM calculation for the 2005 M w 8.7 Nias-Simeulue, Sumatea earthquake. They found the maximum difference is about 5% and mainly localized near the trench where the topographic gradient is highest.…”
Section: Case Study: Wenchun Earthquakementioning
confidence: 99%
“…Conversely, the consideration of a strong slab (a slab with increased rigidity) in the coseismic inversion was shown to lead to a decrease in inferred seismic moment compared to a homogeneous model (Hsu et al 2011;Kyriakopoulos et al 2013). Consideration of surface topography and lateral heterogeneity from seismic tomography was also found to lead to a better fit to the observed coseismic surface displacements (Pulvirenti et al 2014;Romano et al 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Thus, for the same slip, the movement of the hanging wall should increase (cf. Hsu et al 2011). Both effects exist in the HOM → LYR and LYR → SLAB steps.…”
Section: Forward Testsmentioning
confidence: 99%
“…As well known in literature (e.g., Cattin et al, 1999;Masterlark 2003;Aloisi et al, 2011;Hsu et al, 2011), the simple analytical model approach (homogeneous, isotropic, Poisson-solid half-space assumption) has in fact strong limitations and introduces significant displacement prediction errors (with respect to measurement uncertainties). In particular, Cattin et al (1999) found that rigidity contrasts, existing within the upper crust can increase the horizontal displacements for a given slip model by up to 40%.…”
Section: Introductionmentioning
confidence: 99%